2020
DOI: 10.1159/000507941
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fabric Containing Chamaecyparis obtusa Essential Oil on Atopic Dermatitis-Like Lesions: A Functional Clothing Possibility

Abstract: Background: Essential oil derived from Chamaecyparis obtusa (EOCO) has been used as an alternative treatment for allergy-related diseases due to its immune-modulating characteristics. Clothing has the longest and most intense contact with human skin, and functional fabrics with intrinsic properties have been increasingly implemented in medical applications. Specially designed fabrics may support atopic dermatitis (AD) treatment. In this study, the effects of fabric containing EOCO on AD were investigated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The Chamaecyparis obtusa essential oil has been shown to inhibit DNCB-induced AD-like lesions in BALB/c mice through inhibition of Th1/Th2 cytokine overexpression and IgE in both lymph node and spleen [ 80 ]. In addition, in NC/Nga mice, treatment with a fabric saturated with the essential oil produced a significant decrease in the SCORAD score with modifications in transepidermal water loss and serum IgE levels, a reduction in epidermal proliferation and changes in filaggrin, involucrin, and loricrin expression [ 81 ]. The antiatopic effect was also confirmed by Yang et al, who showed that volatile organic compounds from Chamaecyparis obtusa cause inhibition of pathological dermal changes, decrease mast cell infiltration, reductions in serum IgE levels and inhibition of IL-6 and IL-1β in a dose-dependent manner [ 82 ].…”
Section: Antimicrobial and Antivirus Activitymentioning
confidence: 99%
“…The Chamaecyparis obtusa essential oil has been shown to inhibit DNCB-induced AD-like lesions in BALB/c mice through inhibition of Th1/Th2 cytokine overexpression and IgE in both lymph node and spleen [ 80 ]. In addition, in NC/Nga mice, treatment with a fabric saturated with the essential oil produced a significant decrease in the SCORAD score with modifications in transepidermal water loss and serum IgE levels, a reduction in epidermal proliferation and changes in filaggrin, involucrin, and loricrin expression [ 81 ]. The antiatopic effect was also confirmed by Yang et al, who showed that volatile organic compounds from Chamaecyparis obtusa cause inhibition of pathological dermal changes, decrease mast cell infiltration, reductions in serum IgE levels and inhibition of IL-6 and IL-1β in a dose-dependent manner [ 82 ].…”
Section: Antimicrobial and Antivirus Activitymentioning
confidence: 99%